Damage Evolution of Granite under Ultrasonic Vibration with Different Amplitudes - Junpeng Han; Dajun Zhao; Shulei Zhang; Yu Zhou (Shock and Vibration)
As a type of ultra-high frequency loading, ultrasonic vibration is an effective way to break the rock at high rates. Exploring the influence of various factors on the loading effect is essential for its effective application to assist drilling. In this study, the damage evolution of granite under ultrasonic vibration with different amplitudes was investigated. The theoretical and numerical simulation models of rock breaking by ultrasonic vibration were established. The research group applied ultrasonic vibration loading to granite using different amplitudes. The damage characteristics were tested by NMR experiment, and the damage evolution was numerical analyzed by Particle Flow Code software. The result shows that the propagation of cracks is positively correlated with the amplitude of ultrasonic vibration. The increase of amplitude magnifies the generation of transverse cracks, which is conducive to the stripping of rock fragments. A threshold value was found for the amplitude, and fractures show different propagation and expansion characteristics at the higher and lower values. Increasing the amplitude magnifies the stress at the crystal defect and speeds up the crack propagation process. The stress wave generated by ultrasonic vibration inside the rock will attenuate with the increase in depth. Increasing the amplitude value will amplify the stress in the influence area, and decrease the size of the area.